The University of Maine: Playing All Positions in the Policy Game - Ferrini-Mundy, Joan (Maine Policy Review, 2020)
President Joan Ferrini-Mundy outlines how the University of Maine and the University of Maine at Machias are positioned to help further the goals of the 2020–2029 Maine Economic Development Strategy. The central strategies focused on talent and innovation (grow local talent, attract new talent, promote innovation) align well with the university's mission.
Keywords: economic development